2017
DOI: 10.1128/iai.01044-16
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Neuraminidase A (NanA) Promotes Biofilm Formation and Synergizes with Influenza A Virus in Nasal Colonization and Middle Ear Infection

Abstract: Even in the vaccine era, Streptococcus pneumoniae (the pneumococcus) remains a leading cause of otitis media, a significant public health burden, in large part because of the high prevalence of nasal colonization with the pneumococcus in children. The primary pneumococcal neuraminidase, NanA, which is a sialidase that catalyzes the cleavage of terminal sialic acids from host glycoconjugates, is involved in both of these processes. Coinfection with influenza A virus, which also expresses a neuraminidase, exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 63 publications
3
36
0
Order By: Relevance
“…However, there is also a wealth of evidence to show that the role of Nglycan degradation in the host-pathogen interaction extends beyond nutrition. NanA, as the initiator of complex N-glycan degradation, has been identified as a key virulence factor in S. pneumoniae that contributes to adherence [69,78,[80][81][82], biofilm formation [81][82][83][84], tissue invasion [69,85], colonization [82,[86][87][88][89], persistence [86,87], immune Box 2. NanA, as the initiator of complex N-glycan degradation, has been identified as a key virulence factor in S. pneumoniae that contributes to adherence [69,78,[80][81][82], biofilm formation [81][82][83][84], tissue invasion [69,85], colonization [82,[86][87][88][89], persistence [86,87], immune Box 2.…”
Section: Role Of N-glycan Degradation In Virulencementioning
confidence: 99%
See 2 more Smart Citations
“…However, there is also a wealth of evidence to show that the role of Nglycan degradation in the host-pathogen interaction extends beyond nutrition. NanA, as the initiator of complex N-glycan degradation, has been identified as a key virulence factor in S. pneumoniae that contributes to adherence [69,78,[80][81][82], biofilm formation [81][82][83][84], tissue invasion [69,85], colonization [82,[86][87][88][89], persistence [86,87], immune Box 2. NanA, as the initiator of complex N-glycan degradation, has been identified as a key virulence factor in S. pneumoniae that contributes to adherence [69,78,[80][81][82], biofilm formation [81][82][83][84], tissue invasion [69,85], colonization [82,[86][87][88][89], persistence [86,87], immune Box 2.…”
Section: Role Of N-glycan Degradation In Virulencementioning
confidence: 99%
“…The role of NanA in pneumococcal virulence was first investigated following reports that tissues exposed to S. pneumoniae demonstrated removal of Neu5Ac residues and exposure of the underlying glycan receptor [71,72], and that in vitro treatment of chinchilla tracheas with neuraminidase increased S. pneumoniae adherence [74]. Since then, a number of studies have investigated the effect of NanA on pneumococcal adherence; however, results have been conflicting [69,77,78,[80][81][82][83][84]. Inhibition of the neuraminidase activity of NanA has been reported to partially reduce adherence [69,81], but, using truncated versions of NanA, the majority of the contribution of NanA to adherence and invasion has been mapped to its CBM domain [69] (Box 1).…”
Section: Trans-a-(2?3)neuraminidasementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported a substantially reduced bacterial burden in the lungs of mice infected intranasally with nan A and/or nan B gene deletion mutant strains and improved host survival [39,40,68]. NanA was shown to contribute to nasopharyngeal colonisation [41,43,68–70]. However, these findings contrast to several other publications, where no such effects were observed in vivo [28,55,71–73].…”
Section: Discussionmentioning
confidence: 81%
“…This influences the quorum signaling pathway and can result in the development as well as the establishment of biofilms . Biofilms can be particularly pathogenic in the case of OM, as the infections are polymicrobial and can hence create synergistic reactions, increased growth of organisms, antimicrobial tolerance, increased virulence and persistence, as well as exaggerated levels of exopolysaccharide (EPS) . Biofilms have been found to be associated with adenoid hypertrophy and middle ear effusion .…”
Section: Immunologic Evasionmentioning
confidence: 99%